The Influence Of Learning From The Internet On Innovative Behaviour. The Role Of Creative Self-Efficacy As Mediator Among Travel Agents - Mustapa, Zuhaina (2021)
Travel agents in Malaysia face challenges in exploring opportunity and being innovative due to its limitation as a small and medium enterprise. Advances in internet technologies such as search engine, social media and other internet communication channels have created opportunities to travel agents to learn new thing and improving their service performance to tourists. The purpose of this study is to investigate the relationship between learning from the Internet tools such as search engine, Facebook, Twitter and e-mail and innovative behaviour. This research is also investigate the mediating effects of creative self-efficacy in the relationship between learning from the Internet and innovative behavior. At the same time, the role of technological support and curiosity as a moderator in the relationship between learning from the Internet and innovative behaviour are also examined. This research is a quantitative research, where data were collected using questionnaires. The research data were analysed using SPSS. From the findings, it was found that Twitter has positive significant relationship with innovative behaviour. Creative self-efficacy mediates the relationship between learning from the Internet and innovative behaviour. Meanwhile, infrastructure support was found to moderate a relationship between Facebook and innovative behaviour. The role of perceptual curiosity was found as a moderator in a relationship between Facebook and innovative behaviour. The results of this study indicated a positive sign to the future of travel agents by acknowledging the usage of the Internet as a medium of communication and knowledge exploration, are capable to increase innovative behaviour among travel agents.